Peningkatan Hasil Belajar PAI Menggunakan Model Problem Based Learning di Kelas VII.2 UPTD SMPN 1 Kecamatan Mungka - Nurhasanah Nurhasanah; Syawaluddin Syawaluddin; Deslita Deslita; Azimatul Husna; Selvi Yanti; Nur Arifah (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) on the material of prayer and prostration in class VII.2 UPTD SMPN 1 Mungka District through the application of the Problem Based Learning (PBL) model. The background of this study is the low learning outcomes of students, where only 46% of students achieved learning completeness in the pre-cycle, with 15 students (54%) not completing. This is thought to be caused by the use of learning models that do not actively involve students in the learning process, so that students do not understand the material deeply. To overcome this problem, the PBL model is applied which focuses on student involvement in solving real problems and interactive learning. The research method used was classroom action research (PTK), which was conducted in four cycles. The subjects of this study were students of class VII.2 UPTD SMPN 1 Mungka District, totaling 28 students. The results showed a significant increase in student learning outcomes. In cycle I, the number of students who were complete increased to 64% (18 students), while 10 students (36%) were not complete. The improvement continued in cycle II with 78% (22 students) complete and 6 students (22%) not complete. In cycle III, 89% (25 students) were complete and 3 students (11%) were not complete. Finally, in cycle IV, all students (100%) achieved mastery out of 28 students present. The results of this study showed that the application of the PBL model not only increased students' engagement, but also their understanding of PAI materials. Thus, the application of the PBL model proved effective in improving the quality of PAI learning in this school.